Potential health benefits of Nigella sativa on diabetes mellitus and its complications: A review from laboratory studies to clinical trials - Adam, Siti Hajar; Mohd Nasri, Noor; Kashim, Mohd Izhar Ariff Mohd; Abd Latib, Erny Haslina; Ahmad Juhari, Muhammad Amirul Aiman; Mokhtar, Mohd Helmy (Frontiers in Nutrition, 2022)
This review aims to gather and summarise up-to-date information on the potential health benefits of Nigella sativa (NS) on diabetes mellitus (DM) and its complications from different animal models, clinical trials and in vitro studies. DM is one of the most prevalent metabolic disorders resulting from chronic hyperglycaemia due to problems in insulin secretion, insulin action or both. It affects people regardless of age, gender and race. The main consequence of DM development is the metabolic dysregulation of glucose homeostasis. Current treatments for DM include pharmacological therapy, insulin and diabetic therapy targeting β cells. Some of these therapeutic approaches are promising; however, their safety and effectiveness remain elusive. Since ancient times, medicinal plants have been used and proven effective against diseases. These plants are believed to be effective and benefit physiological and pathological processes, as they can be used to prevent, reduce or treat multiple diseases. Nigella sativa Linn. is an annual indigenous herbaceous plant belonging to Ranunculaceae, the buttercup family. NS exhibits multifactorial activities; it could ameliorate oxidative, inflammatory, apoptotic and insulinotropic effects and inhibit carbohydrate digestive enzymes. Thus, this review demonstrates the therapeutic potential of NS that could be used as a complement or adjuvant for the management of DM and its complications. However, future research should be able to replicate and fill in the gaps of the study conducted to introduce NS safely to patients with DM.